Analysis of the formation of laws and regulations in the Indonesian legislation hierarchy - Tutut Ferdiana Mahita Paksi (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
The hierarchy of laws and regulations, as stipulated in Article 7 of Law No. 12 of 2011, shows the types and levels of laws and regulations in force in Indonesia. In addition to the hierarchy regulated in Article 7, Article 8 paragraph (1) of Law No. 12 of 2011 also regulates other types of laws and regulations that are legally recognized. The existence of laws and regulations in Article 8, paragraph (1) has reaped a number of problems. One of them is the position of the regulation in the hierarchy of laws and regulations and the identification of which state ministries/institutions are entitled to issue regulations as referred to in Article 8 paragraph (1) of Law No.12 of 2011.  This paper is a normative research study that uses a conceptual approach and a statutory approach. The results showed that the types of laws and regulations recognized according to Article 8 paragraph (1) of Law No. 12 of 2011 should only include Bank Indonesia Regulations, Ministerial Regulations, and Regional Head Regulations. Furthermore, the existence of Article 8 paragraph (1) will have an impact on the ambiguity of the preparation of laws and regulations based on the concept of Good Regulatory Practices.